Дослідження взаємодії та впливу суспільства на поведінку, ментальний стан, формування лідерських якостей людей та міжособистісних відносин - Галушка, Зоя Іванівна; Карп, Олександр Дмитрович; Тимчак, Віра Степанівна (Canadian Institute For Knowledge Development, 2025)
The study is devoted to the analysis of the influence of the social environment on the mental state, behavior, development of leadership qualities and formation of interpersonal interactions of the individual in the context of modern socio-cultural transformations. The key role of social support as a stress buffer and a factor of psycho-emotional stability, which directly affects cognitive and affective reactions, self-esteem and the ability to social adaptation, is established. The relationship between the perception of support, stress level and overall personality functioning in the youth environment, which is most vulnerable to the negative impact of social isolation, digital fragmentation and reduced intensity of interpersonal connections, is considered. The research methodology was based on a combination of quantitative and qualitative approaches: content analysis, statistical interpretation of standard coefficients, use of the multiple growth formula, and secondary analysis of empirical data. Five main domains of influence of the social environment were identified: mental state, behavioral regulation, leadership potential, interpersonal interaction, and adaptability, which were analyzed in the context of psychological mechanisms – emotional stability, self-control, self-esteem, and the level of social involvement.
Exploring the Influence of Social Environment on Mental Health, Behavioral Patterns, Leadership Development, and Interpersonal Relationships Among Youth in a Digitalized Society.
Keywords: Social security, Sustainable development, Social protection, Gender equality, Human and social capital